(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
Diabetes mellitus is a public health problem which leads to serious complications over time. Experimentally, many herbs have been recommended for treating diabetes. In most cases, however, the recommendations are based on animal studies and limited pieces of evidence exist about their clinical usefulness. This review focused on the herbs, the hypoglycemic actions of which have been supported by three or more clinical studies. The search was done in Google Scholar, Medline and Science Direct databases using the key terms diabetes, plants, herbs, glucose and patients. According to the clinical studies, Aegle marmelos, Allium cepa, Gymnema sylvestre, Momordica charantia, Ocimum sanctum, Nigella sativa, Ocimum sanctum, Panax quinquefolius, Salacia reticulate, Silybum marianum and Trigonella foenum-graecum have shown hypoglycemic and, in some cases, hypolipidemic activities in diabetic patients. Among them, Gymnema sylvestre, Momordica charantia, Silybum marianum and Trigonella foenum-graecum have acquired enough reputation for managing diabetes. Thus, it seems that physicians can rely on these herbs and advise for the patients to improve management of diabetes.